2019
DOI: 10.1002/mawe.201900034
|View full text |Cite
|
Sign up to set email alerts
|

On the microstructure and the origin of intermetallic phase seams in magnetic pulse welding of aluminum and steel

Abstract: The microstructure of aluminum‐steel compounds fabricated by magnetic pulse welding are investigated. Electron backscatter diffraction, energy dispersive x‐ray spectroscopy and scanning electron microscopy revealed the existence of several different phases along the weld seam. While one layer could be identified as aluminum solid solution, a very thin layer close to the steel side of the compound eluded detailed characterization by scanning electron microscopy techniques. Transmission electron microscopy and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…MPW tests were performed in vacuum, with diverse collision conditions to suppress the interaction with air, for a better-quality process monitoring. Böhme et al [19] reported on the microstructure of aluminium-steel specimens produced by MPW. As one layer could be identified as Al solid solution, a very thin layer close to the steel side of the compound was found.…”
Section: Introductionmentioning
confidence: 99%
“…MPW tests were performed in vacuum, with diverse collision conditions to suppress the interaction with air, for a better-quality process monitoring. Böhme et al [19] reported on the microstructure of aluminium-steel specimens produced by MPW. As one layer could be identified as Al solid solution, a very thin layer close to the steel side of the compound was found.…”
Section: Introductionmentioning
confidence: 99%